A note on inflation persistence - Steinar Holden; John C. Driscoll (University of Oslo, Department of Economics, 2001)
In an important paper, Fuhrer and Moore (1995) showed that Taylor (1980)'s staggered wage setting model does not exhibit persistence in inflation; they proposed a simple modification, in which workers cared about the real wages of other workers, which solves this problem. However, we argue that the key part of Fuhrer and Moore's model is not that workers care about the real wages of other workers, but that workers are assumed to care about the past real wages of other workers. When that assumption is replaced by the assumption that workers care about current real wages of other workers, the Fuhrer and Moore model reverts identically to the Taylor model. We also show that a simple model in which workers care about their own past real wages, e.g. because unemployment insurance depends on past wages, as noted in Blanchard and Katz (1999), generates negative autocorrelations in inflation.
Keywords: E31; E3; E5; 330; Inflation persistence; Inflation; Geldpolitik; Tarifpolitik; Schätztheorie; Theorie